Optimal power management for LV distribution feeders with finely distributed PV and co-located storage - Jayasekara, Nadeeshani; Masoum, Mohammad Sherkat; Wolfs, Peter (IEEE, 2013)
Integrating distributed PV systems with co-located storage allows the simultaneous management of the feeder voltage profile and losses while significantly raising the limits on PV penetration. A large distributed storage capability can be managed to provide these functions in addition to the normal storage benefit of limiting or shifting the peak demand. In this paper, a real power management optimization method has been presented that improves the voltage profile of a test feeder with finely distributed PV while minimizing system losses. The results show the effect of storage on the feeder voltage profile, the diurnal differences in storage behavior at the head and the far end of the feeder and provide insight into the economic sizing and periodic daily operation of storage.